The problem of vaginal adenosis - Leffall, Jr., Lasalle (2015)
The National Cooperative Diethylstilbestrol Adenosis (DESAD) Project has completed the major portion of its enrollment phase with the examination of more than 300 daughters of women taking synthetic non steroidal estrogens (denotes DES) during pregnancies occurring from the early 1940's to the mid 1960's. The aims of the Project were to fill urgent needs for information on the prevalence and incidence of structural and epithelial abnormalities of neoplastic changes and their complications in these women.